Genotypic Differences in Dry Weight Accumulation, N Assimilation and Redistribution, and the Effects on Seed Yield and Protein Content in Faba Beans - B. Benong, Masahuling; W. E., Peat (Universiti Putra Malaysia Press, 1994)
This experiment was conducted to study the effects of genotypic differences in dry weight accumulation, N assimilation and redistribution, and N redistribution efficiency of different plant parts on seed yield and protein content among three faba bean cultivars, using a randomized complete block design. The total dry weight accumulated in different growth stages showed significant differences among cultivars during vegetative growth and early flowering, and during flowering and early seed filling, but not during seed filling. N was assimilated throughout growth but a large quantity was assimilated during seed filling ranging from 47.66 to 56.50% of the total plant N. The redistribution ofN from leaves, stems and pod walls to the seeds ranged from 26.66 - 31.42 %, 6.89 - 11.05% and 12.24 - 20.51 % of the seed N content, respectively. The remaining seed N content was assimilated during seed filling which accounted for 40.04 - 52.15 %. High Protein content in seeds seemed to be due to greater N assimilation during seed filling rather than to the N redistribution efficiency from the vegetative plant parts.